Dielectric Analysis of PVDF-CNF Conductive Polymer Nanocomposite for EMI Shielding Application - Prasad, Brijesh; Rathi, Vikas; Panwar, Varij (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878383);" role="presentation">Carbon based <span dir="ltr" style="left: calc(var(--scale-factor)*129.98px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958415);" role="presentation">Nano fillers <span dir="ltr" style="left: calc(var(--scale-factor)*180.62px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899502);" role="presentation">polymer nanocomposites are the advance <span dir="ltr" style="left: calc(var(--scale-factor)*350.11px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938933);" role="presentation">polymer <span dir="ltr" style="left: calc(var(--scale-factor)*386.47px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918268);" role="presentation">materials used in electrical <span dir="ltr" style="left: calc(var(--scale-factor)*497.26px); top: calc(var(--scale-factor)*323.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903285);" role="presentation">device <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933044);" role="presentation">applications<span dir="ltr" style="left: calc(var(--scale-factor)*120.26px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93364);" role="presentation">. Among them carbon nanofibers are highly preferred because of their high aspect ratio, long <span dir="ltr" style="left: calc(var(--scale-factor)*504.58px); top: calc(var(--scale-factor)*337.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968248);" role="presentation">fiber <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*350.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941107);" role="presentation">range, high contact surface area, higher electrical conduction with uniform dispersion property. In the present <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*363.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933919);" role="presentation">work we have developed a thin (PVDF-<span dir="ltr" style="left: calc(var(--scale-factor)*233.81px); top: calc(var(--scale-factor)*363.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922521);" role="presentation">CNF) conductive polymer nanocomposite by solvent casting technique. <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925308);" role="presentation">Here we have focused on understati<span dir="ltr" style="left: calc(var(--scale-factor)*219.77px); top: calc(var(--scale-factor)*376.73px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946206);" role="presentation">ng the dispersion effect on electrical conductivity and for electromagnetic <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*389.93px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934376);" role="presentation">interference (EMI). The developed conductive polymer nanocomposite showed uniform dispersion with higher <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*403.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926708);" role="presentation">conductivity and higher dielectric properties. The newly developed composit<span dir="ltr" style="left: calc(var(--scale-factor)*381.31px); top: calc(var(--scale-factor)*403.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921206);" role="presentation">e has significant applications in the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*416.47px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914985);" role="presentation">field of sensor and shielding.